Form that is a Proposed of Procedures for Auditing the Technical Reserves of General Insurances Branches in the Insurance Activity : applied research (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research aims to identify the theoretical framework of technical reserves in the insurance activity and the role of the auditor in verifying the integrity of the estimates of technical provisions (technical reserves) for the branches of general insurance in insurance companies based on the relevant international auditing standards, as a proposed audit program has been prepared in accordance with international auditing standards that enable the auditor to express a sound opinion on the fairness of the financial statements of these companies , The research has reached many conclusions, the most important of which is the existence of deficiencies in the audit procedures of insurance companies, as the audit program of those companies did not include the existence of detailed procedures to verify the integrity of the estimates of technical allocations as well as to verify that the company complies with the laws and instructions in this regard and thus reflected on the entire audit process and expressing an incorrect opinion towards the financial statements The research also reached many recommendations, the most important of which is the need for detailed procedures by the auditor to verify the integrity of the estimates of technical provisions There are no distortions in those estimates.